Pronunciation Learning Strategies and Motivation: Their Impact on second Language Speech of Japanese EFL Learners - Abe, Hideki (Research in Language, 2025)
Despite increased academic interest in the factors related to individual differences in second language (L2) pronunciation, little is known about how motivated learners utilise pronunciation learning strategies (PLS) to master the target language sound system. Grounded in the self-regulated learning model, this study examined the interplay between PLS and motivation in shaping L2 comprehensibility among 103 learners in Japan. The participants completed a questionnaire that assessed their individual differences in PLS and motivation and undertook a test that measured their L2 comprehensibility. An exploratory factor analysis revealed a two-factor model consisting of PLS and motivation, which was further analysed using Pearson correlation and structural equation modelling. The analysis showed a statistically significant correlation between PLS and L2 comprehensibility, and between motivation and PLS, whereas the correlation between motivation and L2 comprehensibility was not statistically significant. The structural analysis revealed that motivation exerted a significant effect on L2 comprehensibility through PLS, with PLS being a predictor of L2 comprehensibility. Highlighting the often neglected importance of PLS, the findings suggest that the participants were motivated and goal-oriented, which led to their use of PLS. This implies that PLS use and motivation were significant factors in improving L2 comprehensibility in the classroom.